Let Death Bear Witness: A Comparative Analysis of Surdas and Nirmala - SUWANNATHIP, SASASIRI; PRASITNOK, SOLOS (เสฏฐวิทย์ปริทัศน์, 2026)
This research aims: The first, to examine the dimensions of discrimination, humiliation, and exploitation endured by Surdas from Rangabhumi (1925) and Nirmala from Nirmala (1927), two seminal characters from Munshi Premchand’s Hindi novels; the second, to analyze the tragic trajectories that culminate in their deaths; and the third, to conduct a comparative investigation of both characters through the integrated lens of Dalit consciousness and tragic aesthetics. This research is a documentaryresearch employing qualitative textual analysis through a synthesized theoretical framework of Dalit Studies and classical Tragedy Theory, drawing upon Ambedkarite thought, Sharankumar Limbale’s Dalit aesthetics, Aristotelian tragic theory, and Raymond Williams’s concept of modern tragedy. The research results found that: 1) Regarding discrimination, humiliation, and exploitation, both Surdas and Nirmala, despite their disparate social positions, endure systematic oppression mediated through structures of caste, class, gender, and colonial modernity. Surdas, as a blind beggar, experiences spatial marginalization and economic dispossession through caste hierarchy and industrial capitalism. Nirmala, as a young woman without dowry, suffers commodification through the patriarchal institution of mismatched marriage. Both protagonists embody what this study terms “structural dalithood,” a state of being crushed, marginalized, and rendered voiceless by hegemonic social structures. 2) Regarding the tragic trajectories culminating in their deaths, their deaths function not merely as narrative denouements but as epistemic acts exposing the violence of patriarchy, capitalism, and caste-inflected social hierarchies. The tragic flaw (hamartia) inheres not in the protagonists but in the social architecture—the caste-class nexus for Surdas and the patriarchal dowry system for Nirmala—constituting “structural hamartia.” 3) Regarding the comparative analysis, both protagonists converge as “ordinary” tragic figures whose suffering derives from structural rather than individual causes, and both texts perform a testimonial function bearing witness to violence rendered invisible by dominant discourse. However, they diverge in resistance modalities: Surdas articulates active opposition in public space, while Nirmala’s resistance remains interior and confined to domestic space. This study contributes to comparative literature by proposing a methodological synthesis bridging Western tragic theory with indigenous Indian critical frameworks.